Trabalhando com modelos didáticos: correlacionando processo de duplicação do DNA com a divisão celular e os aspectos citogenéticos da meiose com as leis de Mendel - Fonseca, Vanderson Lizt Meneses (2019)
One of the major difficulties faced by high school biology teachers is that subjects that require students imagination and abstraction to understand certain biological processes, often because they involve microscopic and molecular structures, are satisfactorily understood. Didactic models are tools where the teacher can use concrete materials that represent microscopic structures and molecules of the intracellular environment, in order to facilitate the teaching and learning processes. Although there are some studies proposing the making of models for the study of cell reproduction, specifically cytogenetic aspects are little addressed in these models. In order to add contributions to this methodological approach, this work aimed to experiment the making and use of models that associate the model. DNA duplication process with cell division, as well as the identification of Mendel's laws in cytological events of meiosis and their correlation with genetic variability in gamete formation. This project was developed with first and third year high school students from a public school in the city of Parnamirim in the state of Rio Grande do Norte. This study was carried out in the following steps: investigation of a possible prior knowledge of cytogenetic aspects associated with cell division processes; theoretical exposition of the themes; workshops to build models that focus on the association of the DNA replication process with cell division; making models that correlate meiosis division with Mendel's laws and a final assessment of students' acceptance of the proposed methodology and understanding of the topics addressed. The results showed that the use of models is an excellent didactic tool to improve students' interaction and participation in classes, motivating them to have an understanding of the contents proposed in the workshops. In the analysis of the students' level of satisfaction in relation to both workshops, it was observed that all (100%), both the 1st and 3rd students, affirmed that the workshops with models made the classes more interesting, improving the interest in the subject. Given these results, scripts were prepared from both didactic workshops to be available as methodological tools for high school biology teachers.